The Difference Of Endorphin Massage And Effleurage Massage On The Back Pain Of Pregnant Women In The Third Trimester In The Working Area Of The Kembiritan Banyuwangi Health Center - Kristanti Dwi Utami; Indah Christiana; Maya Primayanti (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Back pain, particularly in the lumbosacral region, is a common issue among women in their third trimester of pregnancy. This discomfort tends to become more pronounced as the pregnancy progresses. Without prompt intervention, this condition can lead to persistent pain until postpartum. Endorphin massage and effleurage massage are alternatives to help alleviate back pain in pregnant women during their third trimester. This study aimed to explore the effectiveness of endorphin massage versus effleurage massage in alleviating back pain among women in their third trimester of pregnancy in the working area of the Kembiritan Banyuwangi Health Center in 2023. This study utilizes a pre-experimental methodology, employing a two-group pretest-posttest design. It targets the entire population of third trimester pregnant women suffering from back pain, totaling 99 individuals. The sampling technique uses purposive sampling and resulting in a total of 60 pregnant women who are then divided into two treatment groups, namely group 1 endorphin massage and group 2 effleurage massage then will be tested using the Wilcoxon test and Mann Whitney test. The findings of the study determined using the Wilcoxon test showed a pvalue of < 0.05 both in endorphin massage and effleurage massage which means there is a decrease in pain scales before and after treatment. The Mann Whitney test result found a pvalue of < 0.018 in endorphin massage and a pvalue of < 0.00 in effleurage massage, thus it can be deduced that a difference exists in the reduction of pain levels, and effleurage massage proves to be more efficacious in alleviating back pain among pregnant women in their third trimester. than endorphin massage. Advice for health workers to practice and teach effleurage massage for pregnant women in their third trimester who are dealing with back pain.